(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The study aims to show the impact of internal marketing in tourism companies in terms of enhancing their marketing efficiency, A random sample of 70 managers working in these tourism companies was chosen, and the study relied on a set of statistical methods in presenting, analyzing and interpreting the study information, The study concluded with a set of conclusions, the most important of which was The study demonstrated the lack of interest of the travel agencies surveyed in the marketing activity in general and the lack of interest of senior management in marketing management in particular by not observing the scientific principles in this activity.